Effects of Plantar Mechanical Stimulation on Anabolic and Catabolic Signaling in Rat Postural Muscle Under Short-Term Simulated Gravitational Unloading - Tyganov, Sergey A.; Mochalova, Ekaterina P.; Belova, Svetlana P.; Sharlo, Kristina A.; Rozhkov, Sergey V.; Vilchinskaya, Natalia A.; Paramonova, Inna I.; Mirzoev, Timur M.; Shenkman, Boris S. (Frontiers in Physiology, 2019)
It is known that plantar mechanical stimulation (PMS) is able to attenuate unloading-induced skeletal muscle atrophy and impaired muscle function. However, molecular mechanisms underlying the effect of PMS on skeletal muscle during unloading remain undefined. The aim of the study was to evaluate the effects of PMS on anabolic and catabolic signaling pathways in rat soleus at the early stages of mechanical unloading. Wistar rats were randomly assigned to ambulatory control, hindlimb suspension (HS) for 1 or 3 days, and HS for 1 or 3 days with PMS. The key anabolic and catabolic markers were assessed by western blotting and RT-PCR. Protein synthesis (PS) rate was estimated using SUnSET technique. PMS attenuated a 1-day HS-induced decrease in 4E-BP1, GSK-3β, AMPK phosphorylation. PMS also partially prevented a decrease in PS, phosphorylation of GSK-3β, nNOS and an increase in eEF2 phosphorylation after 3-day HS. PMS during 1-and 3-day HS prevented MuRF-1, but not MAFbx, upregulation but did not affect markers of ribosome biogenesis (18S+28S rRNA, c-myc) as well as AKT phosphorylation. Thus, PMS during 3-day HS partially prevented a decrease in the global rate of PS in rat soleus muscle which was accompanied by attenuation of MuRF-1 mRNA expression as well as changes in GSK-3β, nNOS and eEF2 phosphorylation.